ANALISIS GEJALA PENGARUH AKHIR PEKAN (THE WEEKEND EFFECT) TERHADAP RETURN SAHAM HARIAN LQ45 DI BURSA EFEK INDONESIA - Mellisa Fitri A Andriyani Muzakir (Akademi Akuntansi YKPN Yogyakarta, 2013)
Weekend has strong effect on life behavior, including the stock trading. It is interesting to research that weekend has strong effect to stock exchange. The weekend effects on stock Return had been mostly researched in the overseas stock exchange. Singhal and Bahure (2009) reported that Monday Returns significantly lower than normal daily Returns, and Friday Returns significantly higher than other days so that it can be concluded that there is an existence of weekend effect in India. This research aims to examine the existence of weekend effect in daily stock Returns on LQ45 in the international stock exchange within 2008-2010. The examination took the sample of a company that continuously recorded in the LQ45 within the research period. Taken from the sampling, there are 26 companies that have been registered continuously. The data analysis uses regression, and the hypothesis test uses P-Value. This research proves that weekend effect exists in Indonesia. It is proved that Monday Returns has lower value than the other days. And the Friday Returns has higher value than the other days. So, investors can consider this phenomenon as one of trading strategies. Keywords: Weekend Effect, Stock Returns